The Interpretation of the Verse of Qiwamah from the Perspective of Muhammad Sa'id Ramadhân al-Bûthî: An Analysis of the Book Al-Mar'ah Bain Thughyân Al-Nidzâm Al-Gharbiy wa Lathâ'if Al-Tasyri' Al-Rabbaniy (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2024)
This paper discusses the leadership relations between men and women in Islam, especially in the context of qiwâmah based on the views of Muhammad Sa'id Ramadhân al- Bûthî in the book al- Mar'ah bain Thughyân al- Nidzâm al- Gharbiy wa Lathâ'if al- Tasyri' al- Rabbaniy. The purpose of this study is to examine in depth the meaning of qiwâmah according to al- Bûthî and how this concept is applied in the relationship between husband and wife. This study uses a qualitative method by analysing the main text of the book, as well as other literature related to the issue of qiwâmah. With a moderate and comprehensive tafsir approach, al- Bûthî interprets 'qiwâmah' as the husband's responsibility to protect and nurture the family, not domination over the wife. The husband's leadership is based on his physical advantages and his role as breadwinner, but without demeaning the wife. In essence, wives still have the right to work and contribute economically as long as the work does not burden them.